Generation of self-replicating airway organoids from the cave nectar bat Eonycteris spelaea as a model system for studying host–pathogen interactions in the bat airway epithelium - Louisa L.Y. Chan; Akshamal M. Gamage; Chee Wah Tan; Kai Sen Tan; Jing Liu; Douglas Jie Wen Tay; Randy Jee Hiang Foo; Laurent Rénia; De Yun Wang; Lin-Fa Wang (Emerging Microbes and Infections)
Bats are reservoir hosts for various zoonotic viruses with pandemdic potential in humans and livestock. In vitro systems for studying bat host–pathogen interactions are of significant interest. Here, we establish protocols to generate bat airway organoids (AOs) and airway epithelial cells differentiated at the air–liquid interface (ALI-AECs) from tracheal tissues of the cave-nectar bat Eonycteris spelaea. In particular, we describe steps which enable laboratories that do not have access to live bats to perform extended experimental work upon procuring an initial batch of bat primary airway tissue. Complete mucociliary differentiation required treatment with IL-13. E. spelaea ALI-AECs supported productive infection with PRV3M, an orthoreovirus for which Pteropodid bats are considered the reservoir species. However, these ALI-AECs did not support SARS-CoV-2 infection, despite E. spelaea ACE2 receptor being capable of mediating SARS-CoV-2 spike pseudovirus entry. This work provides critical model systems for assessing bat species-specific virus susceptibility and the reservoir likelihood for emerging infectious agents.